Value of cash and accounting conservatism: The role of audit quality and firm growth - Abbas Ali Daryaei; Yasin Fattahi; Ramazan Hasani; Hamed Sadeqi (Cogent Economics & Finance, 2020)
The primary aim of the present research was to fill the significant gap in the accounting literature, which is widely acknowledged, regarding the association between conservative accounting and the value of cash, particularly in emerging Islamic stock markets. By using a sample including all the firms listed on the Tehran Stock Exchange from 2008 to 2017, we regress the value of cash on accounting conservatism with regard to the moderator role of audit quality (audit tenure, audit opinion, audit size, and earnings management as proxies for audit quality). Generally, the findings not only confirm a positive relationship between accounting conservatism and cash value in the absence of audit quality but also suggest that ignoring the important role of audit quality mechanism can result in wrong conclusions concerning the effect of accounting conservatism on cash value, especially in developing countries such as Iran, due to concentrated government and institutional ownership structures. This cross-sectional analysis based on firm growth leads to the conclusion that analysis regarding the relationship between accounting conservatism and cash value must be taken into account by highlighting the impact of macroeconomic variables and political economy. Furthermore, the findings of the current study suggest that the application of monitoring and controlling theories calls for more inquiry.
Keywords: 330; accounting conservatism; audit quality; firm growth; Value of cash